Natyasastra as a (distorting?) mirror to the epic / puranic mythic image: the question of its dating - Gonc-Moacanin, Klara (Array, 2002)
The first five chapters of the Natyasastra associate the origin of drama with the Vedic god Brahman, but presuppose the epic and puranic mythology, and explain the origin of drama and theatre in the epico-puranic mythic manner. That mythic exposition is, however, carefully styled and represents a mythico-historical introduction to the art of natya. It reveals us in the mythic way even the plots of the fist dramas: the churning of the ocean by the gods and the asuras, and the burning of the three cities of the asuras, connected with the mythology of Visnu and Siva. The links with the Puranas and with the kavya suggest the dating of the Natyasastra in the Gupta age.